2012
DOI: 10.1002/sia.4895
|View full text |Cite
|
Sign up to set email alerts
|

Effects of annealing on the molecular orientation in polytetrafluoroethylene thin films

Abstract: aThe effects of annealing on the molecular orientation in polytetrafluoroethylene (PTFE) thin films evaporated on copper and silicon plates were studied using F K-edge near-edge X-ray absorption fine structure (NEXAFS) spectroscopy. The intensity of the F 1 s ! s*(C-F) transition in the NEXAFS spectrum from a non-annealed PTFE thin film on a copper plate at a glancing X-ray incidence angle was stronger than that at the normal incidence angle. For a thin film annealed at~250 C in a nitrogen atmosphere, the s*(C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Importantly, the fact that excitations arise from two initial states separated by approximately 1 eV (i.e., 2p 1/2 and 2p 3/2 ) makes it somewhat difficult to interpret the sulfur edge since one essentially has two spectra superimposed and shifted by 1 eV . Nevertheless, the NEXAFS spectra are comparable to those obtained elsewhere for the S­(2p) absorption edge of thiophene functional groups. , The characteristic multiplet peak in the spectrum obtained prior to sputtering is indicative of a highly oriented chemical species. , Conversely, the spectra obtained following argon ion sputtering reveals a broad peak, which is suggestive of highly disordered thiophene species, probably randomly orientated polymer molecules in a multitude of chemical states. , This is not unexpected since sulfur in POT is known to exist in a variety of dispersed chemical states, which would cause considerable overlap in the NEXAFS spectra. The net result of this would be a broad, convoluted peak as seen in the spectrum relating to the bulk of the polymer.…”
Section: Resultsmentioning
confidence: 64%
See 1 more Smart Citation
“…Importantly, the fact that excitations arise from two initial states separated by approximately 1 eV (i.e., 2p 1/2 and 2p 3/2 ) makes it somewhat difficult to interpret the sulfur edge since one essentially has two spectra superimposed and shifted by 1 eV . Nevertheless, the NEXAFS spectra are comparable to those obtained elsewhere for the S­(2p) absorption edge of thiophene functional groups. , The characteristic multiplet peak in the spectrum obtained prior to sputtering is indicative of a highly oriented chemical species. , Conversely, the spectra obtained following argon ion sputtering reveals a broad peak, which is suggestive of highly disordered thiophene species, probably randomly orientated polymer molecules in a multitude of chemical states. , This is not unexpected since sulfur in POT is known to exist in a variety of dispersed chemical states, which would cause considerable overlap in the NEXAFS spectra. The net result of this would be a broad, convoluted peak as seen in the spectrum relating to the bulk of the polymer.…”
Section: Resultsmentioning
confidence: 64%
“…22,33 Conversely, the spectra obtained following argon ion sputtering reveals a broad peak, which is suggestive of highly disordered thiophene species, probably randomly orientated polymer molecules in a multitude of chemical states. 34,35 This is not unexpected since sulfur in POT is known to exist in a variety of dispersed chemical states, 36 which would cause considerable overlap in the NEXAFS spectra. The net result of this would be a broad, convoluted peak as seen in the spectrum relating to the bulk of the polymer.…”
Section: ■ Results and Discussionmentioning
confidence: 89%
“…Tripathi et al [14] found the columnar nanostructures were produced by annealing for the PTFE film by magnetron sputtering. Kobayashi et al [15] observed that the molecules in PTFE films were increasingly oriented normal to the substrate surface with increasing annealing temperature. In our previous report, the PTFE film density was greatly increased with increasing annealing temperature and the optimal mechanical properties could be obtained by annealing at 100 °C [16].…”
Section: Introductionmentioning
confidence: 99%